Baicalin Ameliorates Dexamethasone-Induced Osteoporosis by Regulation of the RANK/RANKL/OPG Signaling Pathway - Zhao Y; Wang HL; Li TT; Yang F; Tzeng CM (Dove Medical Press, 2020)
Ye Zhao, 1, 2 Hui-Ling Wang, 1 Tong-Tong Li, 1 Fei Yang, 1 Chi-Meng Tzeng 1 1School of Pharmaceutical Sciences, Nanjing Tech University, Nanjing 211800, People’s Republic of China; 2Jiangsu Synergetic Innovation Center for Advanced Bio-Manufacture, Nanjing Tech University, Nanjing 211800, People’s Republic of ChinaCorrespondence: Ye Zhao; Chi-Meng Tzeng Email zhaoyev@163.com; tzengchimeng@njtech.edu.cnBackground: Osteoporosis is a chronic bone metabolism disorder affecting millions of the world population. The RANKL/RANK/OPG signaling pathway has been confirmed to be the main regulator of osteoporosis. It is of great interest to identify appropriate therapeutic agents that can regulate the RANKL/RANK/OPG pathway. Baicalin (BA) is a well-known traditional Chinese medicine formula against various inflammatory diseases with a proven role of the RANKL/RANK/OPG pathway regulation. However, the potential effect of BA on osteoporosis and the mechanisms underlying this remain unclear. In the present study, we aimed to evaluate the efficacy of BA in the prevention of dexamethasone (DEX)-induced osteoporosis in zebrafish.Methods: In this study, growth and development changes of zebrafish and calcein staining were assessed with a micrograph. The expression levels of RANKL and OPG and transcription factors in response to DEX induction and BA administration were evaluated by Western blotting and qRT-PCR. In addition, the intermolecular interactions of BA and RANKL were investigated by molecular docking.Results: Results show that BA enhances the growth and development of dexamethasone (DEX)-induced osteoporosis in zebrafish larvae. Calcein staining and calcium and phosphorus determination revealed that BA ameliorates mineralization of DEX-induced osteoporosis zebrafish larvae. BA also regulates the expression of RANKL and OPG and hampers the changes in gene expression related to bone formation and resorption under the induction of DEX in zebrafish. It can be inferred by molecular docking that BA may interact directly with the extracellular domain of RANKL.Conclusion: The findings, herein, reveal that BA ameliorates DEX-induced osteoporosis by regulation of the RANK/RANKL/OPG signaling pathway.Keywords: Baicalin, osteoporosis, RANKL, RANK, OPG